Law Enforcement Against Police Officers as Perpetrators of Online Gambling Crimes - Pane, Musa Darwin; Mendisa, Karlina; Putri, Latiffa Rojikin (LEGAL BRIEF, 2024)
Law enforcement against police officers involved in online gambling crimes is a serious issue in Indonesia. Several police officers are involved in online gambling practices, damaging the image of the police institution and reducing public trust. This research uses normative juridical methods with a conceptual approach to identify factors that influence the involvement of police officers in online gambling. These factors include financial stress, easy access to online gambling platforms, environmental influences, and lack of internal oversight. Law enforcement efforts are carried out through internal investigations, investigations, and penal action by implementing sanctions such as dishonorable discharge, transfers in the form of demotions, postponement of promotions, and postponement of education. However, law enforcement against online gambling is still difficult due to developments in information technology used by perpetrators. Increased internal monitoring, awareness and education, implementation of strict sanctions, cross-sector collaboration, and use of technology are needed to overcome this problem. Law enforcement against police officers involved in online gambling is important to maintain the integrity of the police institution and build public trust in law enforcement agencies